Tindak Tutur Ekspresif Pembeli dalam Aplikasi Shopee - Muna Warah; Ria Satini (Jurnal Bahasa dan Sastra, 2022)
This research is motivated by the frequent use of expressive speech acts used by buyers in the assesment column in the Shopee application. Even though the store’s rating is very high, it does not rule out that many buyers are dissatisfied. This dissatifaction can be sourced from problems with shipping goods, choosing colors, sizes, and services provided by the seller. The research focuses on identifying expressive speech acts, including acknowledgments, apologies, and expressions of regret. This type of research is qualitative with analytical descriptive method. The data used are are expressive speech acts of buyers in the form of sentence and words contained in the clothing store assessment column in the Shopee application. The speech act theory used is Searle (1979).  The data analysis technique used the matching method and the agih method. From the result of the study found three forms of expressive speech acts, namely thanking, apoligizing, and regretting. This indicates that the buyer expresses or expresses his heart to the seller about the product that has been purchased.